Lethal Dose Determination of Larvacide Effect of Citrus suhuinensis Peel Extract on Aedes Aegypti Larvae - Wahyu Eko Prabowo; Erma Sulistyaningsih; Dwita Aryadina Rachmawati (Journal of Agromedicine and Medical Sciences, 2023)
Dengue hemorrhagic fever (DHF) is an endemic infectious disease in Indonesia. This disease is caused by dengue virus and transmitted by Aedes aegypti as a vector. Vector control is an important approach to control DHF. Citrus suhuinensis contains active compounds such as saponins, tannins, flavonoids, and D-limonene that can kill Ae aegypti larvae. This study aimed to determine the effectivity and lethal dose of C. suhuinensis peel extract against Ae aegypti larva. This was an experimental study using randomized control-group posttest design on Ae aegypti instar III and IV larvae which were divided into 10 groups, i.e., positive control, negative control, 8 treatment groups of serial doses of 0.01, 0.02, 0.04, 0.06, 0.25, 0.50, 0.75 and 1 %. Each group consisted of 25 larvae. Observations on the larvae were conducted after 24 and 48 hours of treatment. The results showed that C. suhuinensis peel extract has larvicide effect as shown by the Lethal Dose value, i.e., LD50, LD95 and LD99 were 5.77, 9.34 and 11.39%, respectively. In conclusion, the C. suhuinensis peel extract has potential as an Ae. aegypti larvacide.